(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
In the first decades of the twentieth century the inhabitants of greater Buenos Aires created a multitude of civic associations, including popular libraries, in large part to satisfy needs that the state had not met. These civic associations became part of an evolving political system. The growth of the popular libraries coincided with the 1912 opening of the political system when voters became truly important. Porteños displayed a tremendous desire to read, both as a pleasurable pastime but also as a means of achieving upward mobility. To partially satiate their hunger for books, residents created an impressive number of popular libraries that functioned as civic associations. Popular libraries were on the whole inadequate, having few books; open few hours and only paying members could take books home. The libraries did not function, as some have hypothesized, as schools for democracy but were used by politicians of all political parties as a means to create local bases which can help explain why no major effort was made to formalize the system.